Princess of the silver woods - George, Jessica Day, 1976- (Bloomsbury, 2012)
When Petunia, youngest of the dancing princesses, is ambushed by bandits in wolf masks on her way to visit an elderly neighbor, the line between enemies and friends becomes blurred as she and her sisters get a chance to end their family's curse once and for all.